A Strong Protective Action of Guttiferone-A, a Naturally Occurring Prenylated Benzophenone, Against Iron-Induced Neuronal Cell Damage - Yanier Núñez Figueredo; Laura García-Pupo; Osmany Cuesta Rubio; René Delgado Hernández; Zeki Naal; Carlos Curti; Gilberto L. Pardo Andreu (Elsevier, 2011)
Abstract.: Guttiferone-A (GA) is a natural occurring polyisoprenylated benzophenone with several reported pharmacological actions. We have assessed the protective action of GA on iron-induced neuronal cell damage by employing the PC12 cell line and primary culture of rat cortical neurons (PCRCN). A strong protection by GA, assessed by the 2,3-bis(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carbox-anilide (XTT) assay, was revealed, with IC50 values <1 μM. GA also inhibited Fe3+-ascorbate reduction, iron-induced oxidative degradation of 2-deoxiribose, and iron-induced lipid peroxidation in rat brain homogenate, as well as stimulated oxygen consumption by Fe2+ autoxidation. Absorption spectra and cyclic voltammograms of GA-Fe2+/ Fe3+ complexes suggest the formation of a transient charge transfer complex between Fe2+ and GA, accelerating Fe2+ oxidation. The more stable Fe3+ complex with GA would be unable to participate in Fenton-Haber Weiss-type reactions and the propagation phase of lipid peroxidation. The results show a potential of GA against neuronal diseases associated with iron-induced oxidative stress. Keywords:: guttiferone-A, iron, neuroprotection, antioxidant, iron chelation